A comparative structural module study of Balla Lompoa and Ba’anjung - Lianto, Fermanto; Husin, Denny; Trisno, Rudy (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The phenomena of modernization have questioned the world of architecture due to the occurrence of generic design. One of the adaptive solutions to internationalization and standardization without losing architectural roots is to develop architecture by using vernacular modules. This alternative may be suitable to address the stagnancy issue which is still a common problem in developing architecture beyond tradition, including cases like Balla Lompoa and Ba’anjung. The research aims to present a creative fabric by comparing both modules while understanding their pattern and possible connections. Typology is used as a method to raise the pattern, using the grid as the instrument for the case study. The steps are 1) Architectural redrawing, 2) Module extraction, and 3) Algorithm pattern. The output is an architectural algorithm as the patterns. The finding is the similarities and differences in their structural modules. The research novelty is a module guideline for modernizing Balla Lompoa and Ba’anjung, stimulating the development of a hybrid between the two.